Protocol for a phase II, monocentre, double-blind, placebo-controlled, cross-over trial to assess efficacy of pyridostigmine in patients with spinal muscular atrophy types 2–4 (SPACE trial). Issue 7 (30th July 2018) - Stam, Marloes; Wadman, Renske I; Wijngaarde, Camiel A; Bartels, Bart; Asselman, Fay-Lynn; Otto, Louise A M; Goedee, H Stephan; Habets, Laura E; de Groot, Janke F; Schoenmakers, Marja A G C; Cuppen, Inge; van den Berg, Leonard H; et al.
Abstract : Introduction: Hereditary proximal spinal muscular atrophy (SMA) is caused by homozygous loss of function of the survival motor neuron 1 gene. The main characteristic of SMA is degeneration of alpha motor neurons in the anterior horn of the spinal cord, but recent studies in animal models and patients have shown additional anatomical abnormalities and dysfunction of the neuromuscular junction (NMJ). NMJ dysfunction could contribute to symptoms of weakness and fatigability in patients with SMA. We hypothesise that pyridostigmine, an acetylcholinesterase inhibitor that improves neuromuscular transmission, could improve NMJ function and thereby muscle strength and fatigability in patients with SMA. Methods and analysis: We designed a monocentre, placebo-controlled, double-blind cross-over trial with pyridostigmine and placebo to investigate the effect and efficacy of pyridostigmine on muscle strength and fatigability in patients with genetically confirmed SMA. We aim to include 45 patients with SMA types 2–4, aged 12 years and older in the Netherlands. Participants receive 8 weeks of treatment with pyridostigmine and 8 weeks of treatment with placebo in a random order separated by a washout period of 1 week. Treatment allocation is double blinded. Treatment dose will gradually be increased from 2 mg/kg/day to the maximum dose of 6 mg/kg/day in four daily doses, in the first week of each treatment period. The primary outcome measures are a change in the Motor Function Measure and repeated nine-hole peg test before and after treatment. Secondary outcome measures are changes in recently developed endurance tests, that is, the endurance shuttle nine-hole peg test, the endurance shuttle box and block test and the endurance shuttle walk test, muscle strength, level of daily functioning, quality of and activity in life, perceived fatigue and fatigability, presence of decrement on repetitive nerve stimulation and adverse events. Ethics and dissemination: The protocol is approved by the local medical ethical review committee at the University Medical Center Utrecht and by the national Central Committee on Research Involving Human Subjects. Findings will be shared with the academic and medical community, funding and patient organisations in order to contribute to optimisation of medical care and quality of life for patients with SMA. Trial registration number: NCT02941328 .